Pathological Fractures in Rare Bone Diseases: Clinical Cases - Bottai, Vanna; Di Sacco, Federico; Cordoni, Martina; Bettarini, Vittoria; Orsetti, Luca; Parchi, Paolo Domenico; Andreani, Lorenzo (Acta medica Lituanica, 2026)
Rare bone diseases, though uncommon, present significant diagnostic and therapeutic challenges due to their clinical variability and overlapping symptoms with more prevalent conditions. This article describes a clinical case series of three patients with bone fragility fractures caused by rare bone diseases – primary hyperparathyroidism with brown tumor, Gorham-Stout disease, and alkaptonuria – treated at the Department of Orthopedic and Traumatology of Pisa University Hospital between 2018 and 2023. Each case highlights the diagnostic complexities, including inconclusive biopsies, nonspecific imaging findings, and the necessity of a multidisciplinary approach for accurate diagnosis and management. Advanced imaging techniques, such as MRI, CT, and PET, alongside genetic and biochemical analyses, were instrumental in guiding treatment. The cases underscore the importance of early differential diagnosis, which is critical for optimizing both surgical and non-surgical interventions, preventing long-term complications, and improving the patient outcomes. This study emphasizes the need for a collaborative, multidisciplinary approach to effectively diagnose and manage rare bone diseases, ensuring that patients receive timely and appropriate care.
Keywords: pathological bone fractures; Alkaptonuria; Gorham-Stout; primary hyperparathyroidism; rare bone diseases